THE EFFECT OF STOCK SPLIT AND RIGHT ISSUE ON STOCK LIQUIDITY WITH INFLATION AS A MODERATING VARIABLE (STUDY ON COMPANIES THAT CARRIED OUT STOCK SPLIT AND RIGHT ISSUE IN 2017-2021) - Cici Novita; Aisha Hanif (Antis Publisher, 2025)
Objective: The aim of this research is to find out whether the inflation variable moderates stock splits and rights issues on company liquidity. Method: The population in this research are companies that carried out stock splits and rights issues in 2017–2021. The sample was selected using a purposive sampling method and 55 companies were obtained. The data analysis technique used is MRA using SPSS version 23. Results: The results of this test are that stock splits have no effect on company liquidity, rights issues have no effect on company liquidity, and inflation does not moderate stock splits and rights issues on company liquidity. Novelty: This research provides empirical evidence on the moderating role of inflation in the relationship between stock splits, rights issues, and company liquidity — an area that has received limited attention in previous studies, particularly within the 2017–2021 period.